Impact of iodine supplementation and mtDNA mutations on papillary thyroid cancer in saudi women following a vegetarian diet: Impact of iodine supplementation and mtdna mutations on PTC - Abdulaziz Binobead, Manal; H. Al-Qahtani, Wahidah; Alhumaidi Alotaibi, Mashael; M. S. Al-Shamrani, Salha; S. Alghamdi, Hanan; Mostafa Domiaty, Dalia; Ahmed Safhi, Fatmah; Abdullah Alduwish, Manal; Abdulla Alwail, Maha; Abdallah Al-Ghamdi, Nouf; Abdullah Alshahrani, Sawsan; Saeed Al-Qahtani, Wedad (Cellular and Molecular Biology, 2023)
This study examined the influence of iodine supplementation and mitochondrial DNA (mtDNA) mutations in Saudi vegetarian women with papillary thyroid cancer (PTC). Blood and tissue samples from PTC-diagnosed women were analyzed for thyroid function, mtDNA mutations, and immunohistological features. Statistical analysis using Sigmastat was employed to compare thyroid hormone levels and mtDNA mutations between groups. Serum total levels of tri-iodothyronine and thyroid-stimulating hormone were significantly different in patients following a vegetarian diet (P<0.05). Patients with PTC showed an increased frequency of mtDNA mutations in the D-loop region, with significantly higher mutation rates observed in patients following a vegetarian diet compared to other PTC patient groups (P<0.001) and controls (P<0.01). Notably, the mutations were predominantly somatic in Group 3 and germline in Groups 1 and 2. The findings suggest a possible link between iodine deficiency and accelerated PTC tumorigenesis. Furthermore, mtDNA mutations may serve as potential biomarkers for the diagnosis and prognosis of PTC.